How can mental health nurses effectively challenge stigma in the 21st century? - Bates, Laura (2011)
The following dissertation is a critical review of the issues and questions surrounding the ways in which mental health nurses can best address stigma in the 21st century. The work of several key theorists of stigma including Goffman and Link and Phelan are examined and critiqued to provide a clear definition of stigma upon which to base the discussion. The understanding of stigma is used to specifically address the question of how stigma is manifest in wider society and the effect that this has upon the lives of people with mental health problems. Areas covered include the role of the media in perpetuating stigma, the historical basis for stigmatising practices in society, social exclusion and its consequences and finally the impact that this has upon professional practice. The discussion covers the underlying principles of contemporary mental health legislation and critically evaluates the tensions between various strands of legislation, the way in which risk is perceived and managed by practitioners and whether risk averse practice perpetuates stigma against mental health problems. This leads onto the question of how mental health law itself might contribute to the perpetuation of stigma by removing power and responsibility from the hands of service users. Finally the discussion concludes with some suggestion about how a future change in the principles of mental health law might alter the way in which mental health problems are perceived and allow nurses to practice in a way that is less focussed on risk management and more emphasis is given to recovery.